2006
DOI: 10.3354/meps316115
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategies of the copepod Acartia clausi on single and mixed diets of toxic and non-toxic strains of the dinoflagellate Alexandrium minutum

Abstract: The role of mesozooplankton grazers in the development of monospecific algal blooms has often been examined in a scenario in which grazers, depending on their abilities of recognition, select against toxic species and increase grazing pressure on non-toxic species. Here, we present a different ecological scenario in which grazers may select between different strains (toxic and nontoxic) of the same species, which may coexist in similar densities in natural environments prior to bloom initiation. The calanoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…Toxin levels can be manipulated with trace amounts of copepod cues, without the confounding effects of wounding (Selander et al, 2006;Selander, 2007). The results show that corresponding change in transcription is modest, suggesting that toxin induction is not accompanied by a massive amount of confounding factors, as is the case when toxicity is manipulated with, for example phosphate limitation (Barreiro et al, 2006) or the use of different species (Teegarden, 1999). A comparison of the gene expression response associated with grazer-induced elevated toxin formation with expression differences between toxin-producing and non-toxin-producing strains revealed two sequences with expression patterns suggesting involvement in the regulation of toxin content.…”
Section: Resultsmentioning
confidence: 85%
“…Toxin levels can be manipulated with trace amounts of copepod cues, without the confounding effects of wounding (Selander et al, 2006;Selander, 2007). The results show that corresponding change in transcription is modest, suggesting that toxin induction is not accompanied by a massive amount of confounding factors, as is the case when toxicity is manipulated with, for example phosphate limitation (Barreiro et al, 2006) or the use of different species (Teegarden, 1999). A comparison of the gene expression response associated with grazer-induced elevated toxin formation with expression differences between toxin-producing and non-toxin-producing strains revealed two sequences with expression patterns suggesting involvement in the regulation of toxin content.…”
Section: Resultsmentioning
confidence: 85%
“…compressum, Hansen et al (2004) also found that the green Noctiluca preyed actively on Pyrodinium, without exhibiting signs of reduced ingestion or satiation, at values of 540 P. bahamense cells ml À1 , close to the 466 A. minutum cells ml À1 observed in our study for condition 2 (complete darkness). Nevertheless, the ingestion rates of N. scintillans fed on A. minutum are considerably lower than those of the copepod Acartia clausi fed on the same species and the same strain (Frangó pulos et al, 2000;Guisande et al, 2002;Barreiro et al, 2006). As pointed out by Kiørboe and Titelman (1998), this is mainly because Noctiluca preys more efficiently on immobile (diatoms) than on mobile food (for example dinoflagellates).…”
Section: Discussionmentioning
confidence: 83%
“…Many such studies have shown negative responses of grazers to PST-producers. Grazers may change their behavior (Hansen, 1989; Tillmann and John, 2002), reject toxic cells (Teegarden, 1999), or reduce clearance or ingestion rates (Ives 1985; Turriff et al, 1995; Barreiro et al, 2006; Teegarden et al, 2007). Grazer mortality (Hansen, 1989; Tillmann and John, 2002; Tillmann et al, 2007) or decreased reproduction (Dutz, 1998; Frangopulos et al, 2000; Barreiro et al, 2006) can also occur.…”
Section: Introductionmentioning
confidence: 99%
“…Grazers may change their behavior (Hansen, 1989; Tillmann and John, 2002), reject toxic cells (Teegarden, 1999), or reduce clearance or ingestion rates (Ives 1985; Turriff et al, 1995; Barreiro et al, 2006; Teegarden et al, 2007). Grazer mortality (Hansen, 1989; Tillmann and John, 2002; Tillmann et al, 2007) or decreased reproduction (Dutz, 1998; Frangopulos et al, 2000; Barreiro et al, 2006) can also occur. However, some studies have shown no effects of PST producers on at least some of the grazers tested (Teegarden et al, 2001; Colin and Dam, 2003; Kamiyama et al, 2005; Tillmann et al, 2007), or conversely found that only some (but not all) PST-producers had an effect on a particular grazer (Tillmann and John, 2002; Teegarden et al, 2007; Tillmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%